CARACTÉRISATION BIOCHIMIQUE ET MICROBIOLOGIE DE QUELQUES SOUCHES LACTOBACILES ISOLES DE PRODUITS TERROIR. - BENMEHIDI, Nour Elhouda; BENNANI, Bedra (My University, 2022)
THE STUDY OF THE MAIN MORPHOLOGICAL, BIOCHEMICAL AND MICROBIOLOGICAL CHARACTERISTICS OF LACTIC ACID BACTERIA PRESENTS A VARIETY OF RESPONSES WHICH MAY INDICATE A DIVERSITY OF GENERA AND SPECIES. IN OUR WORK, WE OBSERVE A MAJORITY PRESENCE OF LACTOBACILLARY FORMS IN THE TEN ISOLATES OBTAINED FROM DIFFERENT BIOLOGICAL MATRICES, NAMELY FERMENTED WHEAT, FERMENTED TEA, KELILLA-TYPE CHEESE AND GOAT'S MILK BUTTER. INDEED OUR STUDY SHOWS THAT THE LIPOLYTIC ACTIVITY IN ISOLATES OF LACTIC ACID BACTERIA IS LOW, AND THAT THE PROTEOLYTIC ACTIVITY ON THE OTHER HAND IS STRONG IN ISOLATES OF FERMENTED WHEAT, KELIIA AND GOAT'S MILK BUTTER, ALTHOUGH TWO STRAINS OF FERMENTED WHEAT DO NOT HAVE PROTEOLYTIC ACTIVITY, HOWEVER, ALL THE ISOLATES FERMENT MANNITOL AND ARE IMMOBILE, AND THE METABOLIC CHARACTERS DIFFER ACCORDING TO ORIGIN, SPECIES AND GENUS. THIS REMAINS INTERESTING IF ONE SEEKS TO SCREEN THE STRAIN BANK FOR PROBIOTIC STUDIES FOR EXAMPLE OR TO ISOLATE NEW STRAINS WITH TECHNOLOGICAL FUNCTIONS POTENTIALLY APPLICABLE IN THE FOOD INDUSTRY, DESPITE THE SIMPLICITY OF THESE METHODS IF THEY ARE ASSOCIATED WITH MOLECULAR BIOLOGY TECHNIQUES.
Keywords: lactic bacteria; biochemical tests